Florida’s Agricultural Carbon Economy as Climate Action: The Potential Role of Farmers and Ranchers - Young Gu Her; Tara Wade; Sawssan Boufous; Jehangir Bhadha; Michael Andreu (EDIS)
This article introduces concepts related to carbon sequestration, credits, and markets to help Extension agents, farmers, and concerned residents to better understand how agriculture can help to mitigate climate change, and thus become a part of Florida’s carbon economy. Written by Young Gu Her, Tara Wade, Sawssan Boufous, Jehangir Bhadha, and Michael Andreu, and published by the UF/IFAS Department of Agricultural and Biological Engineering, May 2022.